(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
In the article, the discovery of Drosera rotundifolia on the lower Dniper sands in Kherson region (Ukraine) is described with a short description of the species’ southernmost locality in Ukraine.